2016
DOI: 10.1172/jci80304
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 critically regulates renal potassium handling

Abstract: The mTOR pathway orchestrates cellular homeostasis. The rapamycin-sensitive mTOR complex (mTORC1) in the kidney has been widely studied; however, mTORC2 function in renal tubules is poorly characterized. Here, we generated mice lacking mTORC2 in the distal tubule (Rictorfl/fl Ksp-Cre mice), which were viable and had no obvious phenotype, except for a 2.5-fold increase in plasma aldosterone. Challenged with a low-Na+ diet, these mice adequately reduced Na+ excretion; however, Rictorfl/fl Ksp-Cre mice rapidly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 40 publications
2
61
0
1
Order By: Relevance
“…Recent studies demonstrated the role of PKCα in regulating electrolyte handling in the distal nephron [26]. We next performed Western blotting using phospho-specific antibody that recognizes active PKCα/β (bearing phosphorylation at Thr638/641).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated the role of PKCα in regulating electrolyte handling in the distal nephron [26]. We next performed Western blotting using phospho-specific antibody that recognizes active PKCα/β (bearing phosphorylation at Thr638/641).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to ENaC, it is also important to note that a role for regulation of K + channels themselves, in particular ROMK, cannot be ruled out (46). Indeed, one recent report found that genetic disruption of mTORC2 (via constitutive Rictor knockout) caused hyperkalemia by disrupting both ENaC and ROMK (9). Although this may play a role in chronic regulation, the bulk of evidence supports the idea that acute regulation proceeds predominantly through ENaC-dependent control of the electrical gradient that drives K + secretion (22).…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1, which is a complex of mTOR, regulatory-associated protein of mTOR (Raptor) and several other proteins, regulates cell growth and proliferation and inhibits autophagy by stimulating anabolic processes. mTORC2, which is a complex of mTOR, rapamycin- insensitive companion of mTOR (Rictor) and several other proteins, is thought to regulate potassium and sodium levels in the kidney 48,49 . mTORC1 is considered a nutrient sensor because it can be activated by growth factors, nutrients such as amino acids and glucose, and oxidative stress, triggering pathways that lead to protein synthesis, nucleotide synthesis, lipid synthesis and mitochondrial biogenesis by activating the transcriptional repressor yin and yang 1 (YY1) 46,50 .…”
Section: Nutrient-sensing Pathways In the Kidneymentioning
confidence: 99%